System tworzenia wartości w organizacjach sieciowych na przykładzie ASEA Brown Boveri (ABB) - Dąbrowska-Mitek, Magdalena (Value Creation System in Network Organizations - Case of ASEA Brown Boveri (ABB), 2005)
Continuously rising expectations of customers forces present firms to look for ways of receiving new value. Efficient system of value creating in virtual organizations enables achieving increased sales at lover costs. In this paper the author shows value creating system based on ASEA BROWN BOVERI (ABB).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1078, s. 203-213